THE MANAGEMENT OF INDUSTRIAL INTERNSHIP - Sujarwo Sujarwo; Yetti Supriyati (IJHCM (International Journal of Human Capital Management), 2017)
The research objective was to determine of Industrial Internship consisting of planning, organizing, actuating, controling and monitoring.This is a qualitative research by employing a case study method which was conducted at public vocational senior high school (SMK Negeri 5) Makassar from April 2013 to September 2016. Interviews, document review, and direct observation were taken for data collection while the validity of the data was measured by using triangulation of source and technique. For data analysis, the stages of reduction, data display, and conclusion were used. The results show that 1) Planning of Industrial Internship has not been implemented optimally; such as curriculum validation and mapping the business and industrial were not well-conducted by the school; 2) Organizing aspects of industrial internship were less than optimal implemented, such as arranging of Industrial Internship committee was not equipped clearly with the structuring of tasks, job descriptions and distribution of authority. In addition, appointment of school instructur is simply to accommodate the interests of educators with the principle of equity not competency; 3) In actuating aspect, learning by doing and learning by experience were not optimal since the location of industrial internship did not meet the school's need; 4) Controlling and monitoring Industrial Internship were not optimal as well since the teachers as instructors did not control the students' activities continously. To sum up, the industrial internship conducted in vocational high school must obtain serious attention by the school, industry and government as to improve the students' knowledge and skills. Additionally, the school, industry and government are required to collaborate and synergize optimally for the sake of students' improvement.